THE SELLING SYSTEM OF PRODUCTION BY LOOKING CUSTOMER CHARACTER WITH DATA MINING METHODE (Case Study in PT Ultrajaya Milk Industry & Trading Company) - Susilowati, Dyah; Winarsih, Winarsih (Universitas Gunadarma, 2008)
The advancement of computer technology influences many companies to use computer for data processing. Most of the activites in the company are product selling. Based-on the research at PT. Ultrajaya Milk Industry & Trading Company, their product selling activities are still using manual data processing and the computer usage within the company is not optimum yet. Thus, in this paper, system that can assist product selling activities, especially in providing information by making use of customer character, and swift report generator. The approach related to customer character employs data mining model, even though in this case, the existing database can not be categorized in the level of datawarehouse. Hence, modification of data mining approach has been done to match with the existing data.Keyword(s): Infomation system, Selling, Product.Subject Description : H.2. Database Management | H.2.8. Database Applications | Data mining